Delays in lymphatic filariasis elimination programmes due to COVID-19, and possible mitigation strategies. (30th January 2021) - Prada, Joaquín M; Stolk, Wilma A; Davis, Emma L; Touloupou, Panayiota; Sharma, Swarnali; Muñoz, Johanna; Caja Rivera, Rocio M; Reimer, Lisa J; Michael, Edwin; de Vlas, Sake J; Hollingsworth, T Déirdre
Abstract: Background: In view of the current global coronavirus disease 2019 pandemic, mass drug administration interventions for neglected tropical diseases, including lymphatic filariasis (LF), have been halted. We used mathematical modelling to estimate the impact of delaying or cancelling treatment rounds and explore possible mitigation strategies. Methods: We used three established LF transmission models to simulate infection trends in settings with annual treatment rounds and programme delays in 2020 of 6, 12, 18 or 24 months. We then evaluated the impact of various mitigation strategies upon resuming activities. Results: The delay in achieving the elimination goals is on average similar to the number of years the treatment rounds are missed. Enhanced interventions implemented for as little as 1 y can allow catch-up on the progress lost and, if maintained throughout the programme, can lead to acceleration of up to 3 y. Conclusions: In general, a short delay in the programme does not cause a major delay in achieving the goals. Impact is strongest in high-endemicity areas. Mitigation strategies such as biannual treatment or increased coverage are key to minimizing the impact of the disruption once the programme resumes and lead to potential acceleration should these enhanced strategies be maintained.